THYROID HORMONE THERAPY PRINCIPLES AFTER SURGERY OF THYROID TUMORS - V. E. Vanushko; V. V. Fadeev; P. O. Rumyantsev (Опухоли головы и шеи)
Thyroid hormone administration after thyroid tumors surgery is a part of complex treatment strategy. In case of papillary, follicular and poor-differentiated carcinomas suppressive treatment regime is indicated with target TSH level ≤ 0.1 IU/l. Intensity and duration of TSH suppressive treatment regime depends on tumor recurrence risk group and presence of severe cardio-vascular disease. In case of medullary and anaplastic thyroid cancer require substitutive treatment regime as well as after benign tumor surgery. If patient has been undergone partial thyroid resection by reason of benign tumor the suppressive treatment necessity would be settled in terms of postsurgical TSH level. Thereafter on substitutive or suppressive L-thyroxine treatment patient has achieved target TSH level the further control of it is conducting half in year and annually later.